Managerial Economics ; Ekonomi Managerial dala perekonomian global / Dominick Salvatore ; penerjemah, Ikhsan Setyo Budi ; editor Palpi Wuriarti - Savatore, Dominick; Budi, Ikhsan Setyo; Wuriarti,Palupi (2005)
ilus 26 cm